Recycling organic wastes to agricultural land as a way to improve its quality: A field study to evaluate benefits and risks. (March 2017) - Alvarenga, P.; Palma, P.; Mourinha, C.; Farto, M.; Dôres, J.; Patanita, M.; Cunha-Queda, C.; Natal-da-Luz, T.; Renaud, M.; Sousa, J.P.
Graphical abstract: Highlights: A field study assessed the effects of organic wastes on soil and ryegrass growth. Plant parameters were more positively affected after sewage sludge application. After two years, soil parameters were more positively affected by composts. Soil total and extractable Cd, Cr, Ni and Pb did not increase, but Cu and Zn did. Trace elements in the plant were lower than maximum tolerable levels for cattle. Abstract: A field study was established to assess the effects of a sewage sludge (SS), a mixed municipal solid waste compost (MMSWC) and a compost produced from agricultural wastes (AWC), in a Vertisol, using Lolium multiflorum L. The amendments were applied for two consecutive years: 6, 12 and 24 t dry matter ha −1 for SS, and the amendment doses for MMSWC and AWC were calculated to deliver the same amount of organic matter (OM) per unit area. The amendments had significant beneficial effects on some soil properties ( e.g . soil OM, NKjeldahl, extractable P and K), and on plant productivity parameters ( e.g. biomass yield, chlorophyll, foliar area). For instance, soil OM increased from 0.78% to 1.71, 2.48 and 2.51%, after two consecutive years of application of 24 t dry matter ha −1 of SS, MMSWC and AWC, respectively, while the plant biomass obtained increased from 7.75 t ha −1 to 152.41, 78.14 and 29.26 t ha −1, for the same amendments. On the plant, effects were more pronounced for SS than for both compost applications, a consequence of its higher capacity to provide N to the plant in a readily available form. However, after two years of application, the effects on soil properties were more noticeable for both composts, as their OM is more resistant to mineralization, which endures their beneficial effects on soil. Cadmium, Cr, Ni and Pb pseudo-total concentrations, were not affected significantly by the application of the organic wastes to soil, in all tested doses, neither their extractability by 0.01 M CaCl2 . On the contrary, Cu and Zn pseudo-total concentrations increased significantly in the second year of the experiment, following the application of the higher rate of MMSWC and AWC, although their extractability remained very low (<0.5% of their pseudo-total fraction). Trace elements concentrations in the aboveground plant material were lower than their maximum tolerable levels for cattle, used as an indicator of risk of their entry into the human food chain. Despite these results, it is interesting to note that the SS promoted a significant increase in the foliar concentrations of Cu, Ni and Zn that did not happen in composts application, which can be explained by the reduction of the soil pH, as a consequence of SS degradation in soil. Concluding, if this type of organic wastes were to be used in a single application, the rate could be as high as 12 or even 24 t ha −1, however, if they are to be applied in an annual basis, the application rates should be lowered to assure their safe application ( e.g. to 6 t ha −1 ). Moreover, it is advisable to use more stable and mature organic wastes, which have longer lasting positive effects on soil characteristics.